Pengaruh Kompensasi dan Komunikasi Terhadap Semangat Kerja Karyawan Pada PT. Subur Mekar Abadi Pondok Batu Kabupaten Tapanuli Tengah - Putriwati Laia; Mhd. Shafwan Koto; Riwayani Gultom (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of compensation and communication on employee work motivation at PT. Subur Mekar Abadi, Pondok Batu, Central Tapanuli Regency. This research employed a quantitative approach with a descriptive method. The research sample consisted of 51 respondents, who are employees of the company. The data analysis techniques used include the coefficient of determination test, t-test (partial), and F-test (simultaneous). The results indicate that the coefficient of determination (R²) is 0.653, meaning that 65.3% of the variation in employee work motivation can be explained jointly by the variables of compensation and communication, while the remaining 34.7% is influenced by other factors not examined in this study. The t-test results show that compensation has a positive and significant effect on work motivation (t_calculated = 4.333 > t_table = 2.010; p = 0.000 < 0.05), and communication also has a positive and significant effect on work motivation (t_calculated = 3.199 > t_table = 2.010; p = 0.002 < 0.05). Furthermore, the F-test results reveal that compensation and communication simultaneously have a positive and significant effect on employee work motivation (F_calculated = 45.089 > F_table = 3.19; p = 0.000 < 0.05). Therefore, it can be concluded that compensation and communication positively and significantly influence employee work motivation at PT. Subur Mekar Abadi, Pondok Batu, Central Tapanuli Regency.